2005
DOI: 10.1080/00365520510023549
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of c-myc p64, c-myc p67 and c-erbb-2 in colorectal cancer

Abstract: Fecal colonocytes isolated by somatic cell sampling and recovery (SCSR) technology could be used for the non-invasive assessment of the expression of biomarkers of colon cancer such as c-myc p64, c-myc p67 and c-erbb-2. The expression of c-myc p64 and c-myc p67 in colonocytes showed a significant association with colorectal cancer and may be helpful as a biomarker for the non-invasive detection of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…It should also be taken into account that recent advances in the understanding of the structure and function of the human genome have resulted in a breathtakingly rapid development of such complex disciplines as genomics and proteomics making possible targeted detailed investigation of disease-related gene expression patterns. Presently there are only a few reports describing assess- ment of specific RNA expression in human stool samples 42,64,65 ; however, the opportunity of using directly collected colonocytes for RNA isolation should also be considered as a possible alternative to stool-based techniques.…”
Section: Methodological Approaches To the Isolation And Analysis Of Hmentioning
confidence: 99%
“…It should also be taken into account that recent advances in the understanding of the structure and function of the human genome have resulted in a breathtakingly rapid development of such complex disciplines as genomics and proteomics making possible targeted detailed investigation of disease-related gene expression patterns. Presently there are only a few reports describing assess- ment of specific RNA expression in human stool samples 42,64,65 ; however, the opportunity of using directly collected colonocytes for RNA isolation should also be considered as a possible alternative to stool-based techniques.…”
Section: Methodological Approaches To the Isolation And Analysis Of Hmentioning
confidence: 99%
“…They have been used for breast cancer [17,18], ovarian cancer [19], colorectal cancer [20], esophageal squamous cell carcinoma [21], uveal melanoma [22], urothelial cancer [23], prostate cancer [24], colon cancer [25], Alzheimer's disease [26], neurodegenerative diseases [27,28], brain disorders [29], liver toxicity [30], cystic fibrosis [31], amyotrophic lateral sclerosis and Parkinson's disease [32], and urological malignancies, bladder, and renal cancers [33]. These are by no means all the research articles published about the above diseases.…”
Section: Initial Considerationsmentioning
confidence: 99%
“…The technique allowed recovery of several millions (>40×10 6 /g stool) of viable human colonic cells suitable for investigational or diagnostic purposes as they reflected immediate past history of the gut and its metabolic function (5). Since then, several modifications have been made in the collection medium and purification steps (6,7). Recently, there were attempts to separate colonocytes from stool using immuno-magnetic beads covered with antibody against specific epithelial cell proteins (3,8).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there were attempts to separate colonocytes from stool using immuno-magnetic beads covered with antibody against specific epithelial cell proteins (3,8). Multiple studies have shown feasibility of the colonocyte technique in studying molecular biomarkers of colon cancer (6,7), cancer diagnostics and pathogenesis (9), detection of p53 gene mutations (1,10), and evaluation of the action of bioactive food components on gut epithelia (2). …”
Section: Introductionmentioning
confidence: 99%